2016
DOI: 10.1007/s00464-016-5343-6
|View full text |Cite
|
Sign up to set email alerts
|

Totally laparoscopic total gastrectomy using the overlap method; early outcomes of 50 consecutive cases

Abstract: We reported favorable surgical outcomes of TLTG using the overlap method. It is a feasible and safe option for treatment of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…[15,16] Several studies have shown that the esophagojejunal anastomotic complication ranged from 0 to 6.45% in the functional method, [17,18] whereas few reports have illustrated the use of the overlap method. [19,20] In our perspective, modi ed π-shaped anastomosis, an alternative form of the functional method, has its own advantages theoretically. First, during the common entry hole closure, hand-sewing technique was usually practiced in overlap method, which may result not only in the increasing risk of anastomotic leakage and bleeding but also extend the learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…[15,16] Several studies have shown that the esophagojejunal anastomotic complication ranged from 0 to 6.45% in the functional method, [17,18] whereas few reports have illustrated the use of the overlap method. [19,20] In our perspective, modi ed π-shaped anastomosis, an alternative form of the functional method, has its own advantages theoretically. First, during the common entry hole closure, hand-sewing technique was usually practiced in overlap method, which may result not only in the increasing risk of anastomotic leakage and bleeding but also extend the learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…Studies (33,34) reported that the purse-string suture method was a safe and reliable technique. However, the long operation time, high operation difficulty and high price limit its application (35,36). However, intracorporeal hand-sewn esophagojejunostomy under visualization can not only ensure the tension at the anastomosis but also make the anastomosis more reliable.…”
Section: Discussionmentioning
confidence: 99%
“…Ali et al [115] 2016 CS RPM 58 199.8 ± 57.0 81.6 ± 40. 3 5Wang et al [96] Duan et al [116] Lee et al [117] 2017 LS Overlap 50 144.6 ± 29.9 NA 0…”
Section: Conclusion and Prospectsmentioning
confidence: 99%